The Concept of Extraordinary Crime in Indonesia Legal System: is The Concept An Effective Criminal Policy? - Prahassacitta, Vidya (Humaniora, 2016)
The concept of extraordinary crime was a common concept in Indonesia. Adopts from the concept of the most serious crime in Rome Statute and adjusted with the Indonesian legal system. Then it developed wider and introduced into terrorism, corruption, drug abuse offenses, and child sexual abuse in legislations and Constitutional Court verdicts. The implementation of this concept generated some consequences in drafting and formulating the legislation as part of penal policy. This leads to two legal problems; first, what was the categorization of the concept of extraordinary crime? and second, what were the consequences of the concept extraordinary crime in accordance with penal policy?. Normative law research with literature study method, This was a conducted as the response of both legal problems. Using secondary data from legislation, Constitutional Court verdicts, book and journal, this research concludes that; the concept of extraordinary crime parts of criminal policy does not have any standard for the categorization. Then, as consequences of the implementation of the concept of extraordinary crime in several penal efforts are formulating in legislations. The penalty effort is not limited to criminalization and sentencing aspects but wider and shall be in line with the strategy of crime eradication and welfare protection purposes. To reach the effectiveness of the criminal policy of the concept of extraordinary crime, the penalty effort shall be in line with criminal law principles and human right basic principles.